Increasing Economic Interdependence between China and ASEAN and Its Implications - Ting, Wai (JAS (Journal of ASEAN Studies), 2016)
This paper aims to study the problems and issues of China's relations with ASEAN, which has achieved the establishment of ASEAN Economic Community by 2015. Taking into consideration the institutional framework constituted by the multiple agreements signed between China and ASEAN, howÂ will the development of China-ASEAN relations be influenced by increasing economic interdependence between the two? What will be the difficulties ahead in enhancing trade and investments? Does promoting economic cooperation lead to more mutual trust in the political-strategic arena? China's recent policy in developing "one belt, one road", and Chinese relations to the US-led Trans-Pacific Partnership and their implications to ASEAN will also be examined in this paper.